Method for treating organic pollutants in wastewater by strengthening iron-based amorphous alloy through pre-oxidation activation method
The iron-based amorphous alloy is strengthened by the preoxidation activation method, which solves the problems of low degradation efficiency and long time in the prior art, and achieves efficient degradation of organic pollutants in wastewater, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202510109920.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The prior art has low degradation efficiency, long time, and high equipment requirements when treating azo dye-containing wastewater, making it difficult to meet the demand for low-cost, rapid activation of iron-based amorphous-nano-crystal alloys.
The preoxidation activation method is used to treat the iron-based amorphous alloy, and the specific surface area and catalytic activity of the iron-based amorphous alloy are improved through short-term high-temperature oxidation, thereby enhancing its ability to degrade organic pollutants in wastewater.
It realizes efficient degradation of organic pollutants in wastewater, with simple process, low cost and short time, suitable for continuous operations and the treatment of various organic pollutants.
Smart Images

Figure CN119707080A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sewage treatment, and in particular relates to a method for treating organic pollutants in wastewater by strengthening an iron-based amorphous alloy through a pre-oxidation activation method. Background Art
[0002] With the rapid development of industrialization, especially the prosperity of textile and printing and dyeing industries, millions of tons of azo dyes are used worldwide every year, and hundreds of millions of tons of wastewater containing azo dyes are discharged. The azo dyes in these wastewaters pose a huge threat to aquatic ecosystems and human health due to their high chemical stability and low degradation rate.
[0003] Azo dyes in industrial wastewater are difficult to treat by traditional biodegradation methods due to their complex molecular structure and high chemical stability. Under anaerobic conditions, these dyes may be converted into carcinogenic aromatic amines by microorganisms, increasing environmental and health risks. At present, the methods for treating wastewater containing azo dyes are mainly divided into three categories: physical, biological and chemical. Physical methods such as activated carbon adsorption can separate dyes but cannot degrade azo dyes, and have high operating costs and produce a large amount of sludge that needs to be treated. Biological methods are suitable for the degradation of specific toxic azo dyes and have a narrow scope of application. Chemical methods are favored for their rapid degradation rate and high degradation rate, especially advanced oxidation methods, which degrade pollutants by producing active free radicals.
[0004] Among chemical methods, zero-valent iron reduction and its coupled Fenton oxidation method are effective methods for treating wastewater containing azo dyes. These methods use the hydroxyl radicals produced by the Fenton reaction to degrade azo dyes and generate non-toxic small molecules. However, the degradation efficiency of these methods is easily affected by the environment, has poor stability, and requires a long time to achieve efficient degradation. Pre-oxidation methods, such as ball milling, increasing specific surface area, annealing, etc., can increase the active sites of zero-valent iron and accelerate the degradation of azo dyes, but there is still a certain gap from industrial application.
[0005] Patent CN113201699B discloses an iron-based alloy material and its preparation method and application. The material contains Fe, Si, B, P and C elements and is used for the degradation treatment of azo dye wastewater. However, the patent not only has strict requirements on the alloy composition, Fe: 82% to 83%, Si: 2% to 3%, B: 10% to 15%, P: 2% to 3%, C: 1%, but also the iron-based alloy prepared by the patent needs to be annealed in a high-temperature vacuum at 800 to 850°C to form nanocrystals. The high-temperature annealing requires high requirements on heat treatment equipment and conditions, which increases the cost. In addition, the amount of iron-based alloy material used in the patent is 2g / L, and C1 material is preferred. It still takes more than 30 minutes to achieve a degradation rate of 90% in the degradation of 40mg / L Golden Orange II solution (C t / C0 equals 0.1).
[0006] Patent CN109402369A discloses an iron-based porous material for degrading azo dyes and a preparation method thereof. The porous material is obtained by heat treating an iron-based amorphous alloy precursor and then using dealloying treatment, but the heat treatment process of this method requires a high vacuum of 80mTorr, and in the dealloying process, the concentration and treatment time of the corrosive solution need to be strictly controlled. In addition, the patent only provides the final degradation rate of the porous material for degrading azo dyes, and does not provide the rate of the degradation reaction and the reaction constant.
[0007] Patent CN117943002A discloses an iron-based nanoporous material and its preparation method and application. The iron-based nanoporous material is prepared by annealing and chemical dealloying. However, in this method, under the conditions of 8 g / L of np-SA20, 40 mg / L of Golden Orange II solution concentration and constant temperature of 35°C, it still takes about 30 minutes to achieve a degradation rate of more than 90%.
[0008] Patent CN110918911B discloses an iron-based amorphous alloy strip and its application in the degradation of azo dye wastewater. Although the alloy strip has good corrosion resistance and catalytic degradation activity, the degradation rate of 40 mg / L of azo dye is less than 50% in 10 minutes when 2 g / L of the alloy prepared by this method is used to degrade 40 mg / L of azo dye, and it still takes 50 minutes to achieve a degradation rate of more than 95%.
[0009] Patent CN111170414B discloses a method for degrading wastewater with an iron-based amorphous alloy strip. The degradation rate is increased by ball milling the iron-based amorphous alloy strip for 4-8 hours. When the strip dosage is 10 g / L and the pH is 2-3, it still takes more than 10 minutes to degrade 20 mg / L of Acid Orange 7 to achieve a degradation rate of 90%. (C t / C0 equals 0.1).
[0010] Patent CN112973691B discloses a method for preparing an amorphous-nanocrystalline alloy with a nanostructure, which increases the reaction rate by increasing the specific surface area of the strips. However, the examples show that the degradation rate of organic dye waste liquid with 0.5 g / L nanocrystalline alloy catalyst added after 6 minutes of reaction is only 50%, while it takes more than 30 minutes to achieve a degradation rate of 97%.
[0011] Patent CN107326159B discloses a method for preparing and applying an iron-based nanocrystalline alloy for treating printing and dyeing wastewater containing azo dyes. Iron-based nanocrystals are obtained by annealing an iron-based amorphous alloy. However, the 1K107BN85 strip obtained by annealing at 800°C by this method still requires 10-15 minutes to degrade a 25 mg / L Golden Orange 2 dye aqueous solution at a degradation rate of 90% under the condition of a strip dosage of 10 g / L.
[0012] At present, the efficiency of using iron-based amorphous alloys to degrade printing and dyeing wastewater is still relatively low. The time to complete a 90% degradation rate is generally more than 10 minutes, and the equipment requirements are high, the processing time is long, and the preparation method is relatively complicated. It is difficult to meet the low-cost rapid activation of iron-based amorphous-nanocrystalline alloys, and then achieve rapid degradation of organic pollutants in wastewater. Summary of the invention
[0013] The purpose of the present invention is to provide a method for treating organic pollutants in wastewater by strengthening iron-based amorphous alloys using a pre-oxidation activation method, so as to solve the problems existing in the above-mentioned prior art. Adding an iron-based amorphous alloy that has been pre-oxidized to the wastewater system degrades the organic pollutants in the wastewater; the pre-oxidation treatment method is a short-time high-temperature oxidation method, which has the advantages of simple process, high degradation efficiency, short time required, continuous operation, and the ability to treat a variety of organic pollutants.
[0014] A method for treating organic pollutants in wastewater by strengthening iron-based amorphous alloys using a pre-oxidation activation method comprises the following steps: heating the wastewater containing organic pollutants, adding hydrogen peroxide, adjusting the pH, then adding pre-oxidized iron-based amorphous alloys, reacting under stirring, and degrading the organic pollutants.
[0015] Preferably, the concentration of the organic pollutants in the wastewater is 5-350 mg / L, the amount of hydrogen peroxide added is 1-30 mmol / L, and the amount of pre-oxidized iron-based amorphous alloy added is 0.05-20 g / L.
[0016] Preferably, the pre-oxidized iron-based amorphous alloy is obtained by subjecting the iron-based amorphous alloy to a high-temperature oxidation treatment in air or an atmosphere with an oxygen partial pressure of not less than 0.01 MPa.
[0017] More preferably, the temperature of the high temperature oxidation is 450-850° C., and the time is 6 s-30 min.
[0018] More preferably, the temperature of the high temperature oxidation is 500-800°C.
[0019] Most preferably, the temperature of the high temperature oxidation is 650-750°C.
[0020] More preferably, the iron-based amorphous alloy includes one or more of amorphous strips newly prepared by casting or smelting, strips with partially aged and crystallized surfaces, and waste strips with rusted and oxidized surfaces, and the iron-based amorphous alloy includes silicon, boron and iron, wherein the mass percentage of iron atoms is ≥50%.
[0021] The present invention utilizes high temperature oxidation treatment of iron-based amorphous alloy, and the principle of strengthening iron-based amorphous degradation of organic pollutants in wastewater is as follows: in the pre-oxidation treatment of iron-based amorphous alloy, on the one hand, the oxidation treatment causes the silicon and boron elements inside the iron-based amorphous alloy to diffuse rapidly, forming submicron silicon-rich and boron-rich iron oxide particles on the surface of the strip, thereby increasing the specific surface area of the strip. On the other hand, the iron element inside the strip is precipitated to form nanometer or submicron α-Fe all over the surface and inside of the alloy, increasing the crystal defects such as grain boundaries and phase boundaries inside the alloy, changing the chemical potential on the surface and inside of the strip, thereby promoting the catalytic degradation rate of the alloy; in addition, during the pre-oxidation treatment, the segregation of silicon and boron elements in the iron-based amorphous alloy will introduce residual stress and passivation film inside the strip, thereby facilitating the iron atoms to lose electrons to generate ferrous ions and enter the solution, further promoting the generation of hydroxyl radicals and the degradation rate of organic pollutants.
[0022] Preferably, the heating temperature is 10-80°C, the pH is 2.0-6.5, and the stirring time is 10s-30min. More preferably, the pH is 2.5-5.0, and even more preferably, the pH is 2.9-4.5.
[0023] Preferably, the organic pollutants include one or more of Orange II, methylene blue, rhodamine B, phenol and other organic substances.
[0024] Compared with the prior art, the present invention has the following advantages and technical effects:
[0025] The high-temperature rapid pre-oxidation activation method has an enhancing effect on common commercially available iron-based amorphous alloys and iron-based amorphous alloy strips whose surfaces have been partially aged, rusted and oxidized. In addition, catalytic degradation experiments were carried out under a Fenton-like system. Using 0.5 g / L pre-oxidized iron-based amorphous strips, the degradation rate of Orange II can be achieved by about 95% in just 2 minutes, and Rhodamine B requires 6 minutes of reaction time to achieve a degradation rate of 95%.
[0026] Compared with other surface activation (treatment) methods of iron-based amorphous materials, such as high-temperature vacuum annealing, surface activation and dealloying, the pre-oxidation activation method provided by the present invention has a significant effect on strengthening the degradation of azo dyes by amorphous alloys and is low in cost. According to calculations, the pre-oxidation cost of iron-based amorphous alloys required for degrading printing and dyeing wastewater containing azo dyes by this method is less than 0.5 yuan per ton of wastewater.
[0027] The method provided by the present invention has low requirements for pre-oxidation equipment, is simple to operate, has strong practicality, can continuously and batch-process iron-based amorphous alloys, is easy to promote and industrialize, and is of great significance for achieving water resource recycling, environmental governance, energy conservation and emission reduction, and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0029] Figure 1 (a) is the UV-visible absorption spectrum measured in Example 1, and (b) is the UV-visible absorption spectrum measured in Example 2;
[0030] Figure 2 The degradation rate curves of the 1k107 iron-based amorphous strips activated by pre-oxidation at 650°C in Example 1-2 respectively degraded 20 mg / L Orange II and Rhodamine B dye aqueous solutions over time;
[0031] Figure 3 The color of the Orange II dye aqueous solution in Example 1 changes with time;
[0032] Figure 4 This is a graph showing the color change of the Rhodamine B dye aqueous solution over time in Example 2;
[0033] Figure 5 (a) is the ultraviolet-visible light absorption spectrum diagram measured in Example 3, (b) is the ultraviolet-visible light absorption spectrum diagram measured in Example 4, and (c) is the ultraviolet-visible light absorption spectrum diagram measured in Example 12;
[0034] Figure 6 (a) is the UV-visible absorption spectrum measured in Example 13, and (b) is the UV-visible absorption spectrum measured in Example 5;
[0035] Figure 7 (a) is the ultraviolet-visible light absorption spectrum diagram measured in Example 6, (b) is the ultraviolet-visible light absorption spectrum diagram measured in Example 7, and (c) is the ultraviolet-visible light absorption spectrum diagram measured in Example 8;
[0036] Figure 8 (a) is the ultraviolet-visible light absorption spectrum diagram measured in Example 9, and (b) is the ultraviolet-visible light absorption spectrum diagram measured in Comparative Example 1;
[0037] Fig. 9This is the UV-visible light absorption spectrum obtained in Comparative Example 2;
[0038] Fig.10 The degradation rate curve of Orange II dye aqueous solution in Example 3;
[0039] Fig.11 The degradation rate curve of Orange II dye aqueous solution in Example 4;
[0040] Fig.12 The degradation rate curve of Orange II dye aqueous solution in Example 5;
[0041] Fig.13 The degradation rate curve of Orange II dye aqueous solution in Example 6;
[0042] Fig.14 The degradation rate curve of Orange II dye aqueous solution in Example 7;
[0043] Fig.15 The degradation rate curve of Orange II dye aqueous solution in Example 8;
[0044] Fig.16 The degradation rate curve of Orange II dye aqueous solution in Example 9;
[0045] Fig.17 is a graph showing the degradation rate of the Orange II dye aqueous solution in Example 12;
[0046] Fig.18 The degradation rate curve of Orange II dye aqueous solution in Example 13;
[0047] Fig.19 (a) is the UV-visible absorption spectrum measured in Example 10, and (b) is the degradation rate curve of 1k107 Fe-based amorphous strips activated by pre-oxidation at 650° C. in Example 10 when degrading 20 mg / L Orange II aqueous solution;
[0048] Fig. 20 (a) is the UV-visible absorption spectrum measured in Example 11, and (b) is the degradation rate curve of 1k107 iron-based amorphous strips activated by pre-oxidation at 750°C in Example 11 when degrading 20 mg / L Orange II aqueous solution. DETAILED DESCRIPTION
[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0050] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0054] An embodiment of the present invention provides a method for treating organic pollutants in wastewater by using a pre-oxidation activation method to strengthen an iron-based amorphous alloy, comprising the following steps: heating the wastewater containing organic pollutants, adding hydrogen peroxide, adjusting the pH, and then adding a pre-oxidized iron-based amorphous alloy, reacting under stirring, and degrading the organic pollutants.
[0055] In some embodiments, the concentration of the organic pollutants in the wastewater is 5-350 mg / L, the amount of hydrogen peroxide added is 1-30 mmol / L, and the amount of pre-oxidized iron-based amorphous alloy added is 0.05-20 g / L.
[0056] In some preferred embodiments, the amount of the pre-oxidized iron-based amorphous alloy added is 0.5-10 g / L. Exemplarily, the amount of the pre-oxidized iron-based amorphous alloy added is 0.5 g / L or 10 g / L.
[0057] In some embodiments, the pre-oxidized iron-based amorphous alloy is obtained by subjecting the iron-based amorphous alloy to high-temperature oxidation treatment in air or an atmosphere with an oxygen partial pressure of not less than 0.01 MPa.
[0058] In some embodiments, the high temperature oxidation temperature is 450-850° C., and the time is 6 s-30 min.
[0059] In some preferred embodiments, the temperature of the high temperature oxidation is 500-800°C.
[0060] In some more preferred embodiments, the temperature of the high temperature oxidation is 650-750°C.
[0061] In some embodiments, the iron-based amorphous alloy includes one or more of amorphous strips newly prepared by casting or smelting, strips with partially aged and crystallized surfaces, and waste strips with rusted and oxidized surfaces. The iron-based amorphous alloy includes silicon, boron and iron, wherein the mass percentage of iron atoms is ≥50%.
[0062] In some preferred embodiments of the present invention, the heating temperature is 10-80° C., the pH is 2.0-6.5, and the stirring time is 10 s-30 min.
[0063] In some preferred embodiments, the heating temperature is 10-70°C.
[0064] In some preferred embodiments, the pH is 2.5-5.0;
[0065] In some more preferred embodiments, the pH is 2.9-4.5.
[0066] In some preferred embodiments of the present invention, the organic pollutants include one or more organic substances such as Orange II, methylene blue, rhodamine B and phenol.
[0067] The normal temperature of the present invention refers to 25±2°C.
[0068] Example 1
[0069] 1) Place 0.125 g of Fe-based amorphous 1K107 strip in air at 650°C and let it stand for 5 minutes for pre-oxidation. Take out the pre-oxidized Fe-based amorphous strip and cool it in air for later use.
[0070] 2) Take 250mL of 20mg / L Orange II (Acid Orange 7, AO7) aqueous solution is placed in a 500mL beaker, the beaker is placed in a 30°C water bath, 3mmol / L hydrogen peroxide is added (3mmol hydrogen peroxide is added to each liter of wastewater), the pH value is adjusted to 3 by adding a 5% by mass dilute sulfuric acid solution, the Orange II solution is mechanically stirred at 600r / min, 0.5g / L pre-oxidized iron-based amorphous alloy strips are added, and 4.8mL of Orange II solution is taken at 0s, 30s, 60s, 90s, 2min, 3min, 4min and 6min after the strips are added, filtered through a 0.22μm water-based polyethersulfone (PES) filter membrane, and the solution spectrum is measured by a UV-visible photometer; and at 0min, 0.5min, 1.0min, 1.5min, 2.5min, 4.0min, 6.0min and 9.0min, a photo is taken to record the color change of the dye solution over time, and the degradation rate of Orange II in the solution at different times is calculated and a degradation rate curve is drawn.
[0071] Figure 1 (a) is the UV-visible absorption spectrum measured in Example 1, Figure 2 The degradation rate curves of the 1k107 iron-based amorphous strips activated by pre-oxidation at 650°C in Example 1-2 respectively degraded 20 mg / L Orange II and Rhodamine B dye aqueous solutions over time; Figure 2 It shows that under the above degradation conditions, Orange II (AO7) has been basically degraded after 2 minutes of reaction, with a degradation rate of 93.5%. The degradation rate of Orange II reaches 98.4% after 3 minutes of degradation; and the degradation rate of Orange II reaches 99.5% after 6 minutes of degradation.
[0072] Figure 3 The color of the Orange II dye aqueous solution in Example 1 changes with time. Figure 3 It can be seen that it has completely turned into a colorless and transparent state at 6 minutes.
[0073] Example 2
[0074] The same as Example 1, except that the Orange II aqueous solution was replaced with a Rhodamine B aqueous solution, and 4.8 mL of Rhodamine B solution was taken at 0s, 30s, 60s, 90s, 150s, 4min, 6min, 9min and 12min after the pre-oxidized iron-based amorphous alloy strip was added, respectively, and filtered through a 0.22μm aqueous polyethersulfone (PES) filter membrane, and the solution spectrum was measured by a UV-visible photometer, and photographed at 0min, 0.5min, 1.0min, 1.5min, 2.5min, 4.0min, 6.0min, 9.0min and 12.0min to record the color change of the dye solution over time, and calculate the degradation rate of Rhodamine B in the solution at different times and draw a degradation rate curve.
[0075] Figure 1 (b) is the UV-visible absorption spectrum measured in Example 2, combined with Figure 2 It shows that the degradation of Rhodamine B is basically completed after 6 minutes under this degradation condition, and its degradation rate is 98.1%. After 12 minutes of reaction, the degradation rate of Rhodamine B reaches 99.7%, and the color disappears completely. Figure 4 The color change of the Rhodamine B dye aqueous solution in Example 2 over time is shown in the figure.
[0076] Example 3
[0077] The same as Example 1, except that step 2): 250 mL of an Orange II aqueous solution with a concentration of 150 mg / L is placed in a 500 mL beaker, the beaker is placed in a 40° C. water bath, 12 mmol / L of hydrogen peroxide is added, and the pH value is adjusted to 2.9; the Orange II solution is mechanically stirred at 350 r / min, 2 g / L of pre-oxidized iron-based amorphous alloy strips are added, and 4.8 mL of Orange II solution is taken at 0 s, 30 s, 60 s, 90 s, 150 s, 4 min, 6 min, and 9 min after the strips are added, filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane, and the solution spectrum is measured using a UV-visible photometer, and a color change graph of the dye solution over time is recorded by taking a picture, and the degradation rate of Orange II in the solution at different times is calculated and a degradation rate curve is drawn.
[0078] Figure 5 (a) is the UV-visible light absorption spectrum obtained in Example 3. Fig.10 This is a degradation curve of the Orange II dye aqueous solution in Example 3. Under the degradation conditions, the degradation rate of Orange II is 92.9% after 2.5 minutes of reaction. After 9 minutes, the degradation rate reaches 99.3%. At 9 minutes, the color disappears completely.
[0079] Example 4
[0080] The same as Example 1, except that the 30°C water bath was replaced with a 10°C water bath, 4.8 mL of Orange II solution was taken at 0 min, 1 min, 2.5 min, 4 min, 6 min, 9 min, 12 min and 18 min after the strip was added, and the solution was filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane. The solution spectrum was measured using a UV-visible photometer, and the degradation rate of Orange II in the solution at different times was calculated and the degradation rate curve was plotted.
[0081] Figure 5 (b) is the UV-visible light absorption spectrum obtained in Example 4. Fig.11 This is a curve diagram of the degradation rate of the Orange II dye aqueous solution in Example 4. Under the degradation conditions, the degradation rate of Orange II is 83.1% after 9 minutes of reaction. After 18 minutes, the degradation rate reaches 92.8%.
[0082] Example 5
[0083] The same as Example 1, except that the high temperature oxidation treatment condition is changed from oxidation at 650° C. for 5 min to oxidation at 580° C. for 5 min.
[0084] Figure 6 (b) is the UV-visible absorption spectrum measured in Example 5, Fig.12 This is a degradation curve of the Orange II dye aqueous solution in Example 5. Under the degradation conditions, the degradation rate of Orange II is 87.3% after 6 minutes of reaction. After 9 minutes, the degradation rate reaches 93%.
[0085] Example 6
[0086] 1) Place 0.125 g of Fe-based amorphous 1K101 strip in air at 530°C and let it stand for 5 minutes for pre-oxidation. Take out the pre-oxidized Fe-based amorphous strip and cool it in air for later use.
[0087] 2) Take 250mL of 20mg / L Orange II aqueous solution and place it in a 500mL beaker, put the beaker in a 30℃ water bath, add 3mmol / L hydrogen peroxide, and adjust the pH value to 2.9; use 350r / min mechanical stirring Orange II solution, add 0.5g / L pre-oxidized iron-based amorphous strips, and take 4.8mL of Orange II solution at 0s, 30s, 60s, 90s, 150s, 4min, 6min, and 9min after adding the strips, filter through a 0.22μm water-based polyethersulfone (PES) filter membrane, use a UV-visible photometer to measure the solution spectrum, take pictures to record the color change of the dye solution over time, calculate the degradation rate of Orange II in the solution at different times and draw a degradation rate curve.
[0088] Figure 7(a) is the UV-visible light absorption spectrum obtained in Example 6. Fig.13 This is a degradation curve of the Orange II dye aqueous solution in Example 6. Under the degradation conditions, the degradation rate of Orange II is 96% after 1.5 minutes of reaction. After 9 minutes, the degradation rate reaches 99%.
[0089] Example 7
[0090] The same as Example 6, except that the high temperature oxidation treatment condition is changed from oxidation at 530° C. for 5 min to oxidation at 800° C. for 1 min.
[0091] Figure 7 (b) is the UV-visible absorption spectrum obtained in Example 7. Fig.14 This is a curve diagram of the degradation rate of the Orange II dye aqueous solution in Example 7. Under the degradation conditions, the degradation rate of Orange II is 95.9% after 4 minutes of reaction. After 9 minutes, the degradation rate reaches 99.9%.
[0092] Example 8
[0093] The same as Example 6, except that the high temperature oxidation treatment condition is changed from oxidation at 530° C. for 5 min to oxidation at 460° C. for 5 min.
[0094] Figure 7 (c) is the UV-visible absorption spectrum obtained in Example 8. Fig.15 This is a degradation curve of the Orange II dye aqueous solution in Example 8. Under the degradation conditions, the degradation rate of Orange II is 92.5% after 4 minutes of reaction. After 9 minutes, the degradation rate reaches 98.9%.
[0095] Example 9
[0096] 1) Place 0.25g of Fe-based amorphous 1K107 ribbon in air at 200°C and leave it for 20 minutes to simulate the state of 1K107 ribbon in service for 5-10 years at room temperature. Take out the oxidized Fe-based amorphous ribbon and cool it in air for later use.
[0097] 2) 0.125 g of the simulated waste strips in step 1) were placed in air at 650° C. and allowed to stand for 5 minutes for pre-oxidation activation. The activated iron-based amorphous strips were taken out and cooled in air for later use;
[0098] 3) Take 250 mL of 20 mg / L Orange II aqueous solution and place it in a 500 mL beaker. Place the beaker in a 30°C water bath and add 3 mmol / L hydrogen peroxide to adjust the pH to 3.
[0099] 4) The Orange II solution was mechanically stirred at 350 r / min, 0.125 g of the strip activated in step 2) (0.5 g / L) was added, and 4.8 mL of the Orange II solution was taken at 0 s, 30 s, 60 s, 90 s, 150 s, 4 min, 6 min, and 9 min after the strip was added, and filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane. The solution spectrum was measured using a UV-visible photometer, and the degradation rate of Orange II in the solution at different times was calculated and a degradation rate curve was drawn.
[0100] Figure 8 (a) is the UV-visible light absorption spectrum measured in step 4), Fig.16 This is a graph showing the degradation rate of the Orange II dye aqueous solution in Example 9. Under the degradation conditions, the degradation rate of Orange II is 88.1% after 2.0 minutes of reaction. After 9 minutes, the degradation rate reaches 99.2%.
[0101] Example 10
[0102] 1) Place 2.5280 g of Fe-based amorphous 1K107 strip in air at 650°C and let it stand for 3 minutes for pre-oxidation. Take out the pre-oxidized Fe-based amorphous strip and cool it in air for later use.
[0103] 2) Take 250mL of 20mg / L Orange II (Acid Orange 7, AO7) aqueous solution and place it in a 500mL beaker, put the beaker in a 30°C water bath, add 3mmol / L hydrogen peroxide (3mmol hydrogen peroxide is added to each liter of wastewater), adjust the pH value to 2.8 by adding 5% dilute sulfuric acid solution, mechanically stir the Orange II solution at 600r / min, add 10g / L pre-oxidized iron-based amorphous alloy strips, and take 4.8mL of Orange II solution at 0s, 30s, 60s, 90s, 2min, 3min and 4min after the strips are added, filter through a 0.22μm water-based polyethersulfone (PES) filter membrane, measure the solution spectrum by a UV-visible photometer, calculate the degradation rate of Orange II in the solution at different times and draw a degradation rate curve.
[0104] Fig.19 (a) is the UV-visible absorption spectrum measured in Example 10, Fig.19 (b) is a curve showing the degradation rate variation over time of the 1k107 Fe-based amorphous strip pre-oxidized and activated at 650°C in Example 10 when degrading a 20 mg / L Orange II aqueous solution; Fig.19 (b) shows that under the above degradation conditions, Orange II (AO7) has been basically degraded after 1 minute of reaction, with a degradation rate of 98.0%. The degradation rate of Orange II reaches 98.5% after 2 minutes of degradation.
[0105] Embodiment 11
[0106] 1) Place 0.1316 g of Fe-based amorphous 1K107 strip in air at 750°C and let it stand for 1 minute for pre-oxidation. Take out the pre-oxidized Fe-based amorphous strip and cool it in air for later use.
[0107] 2) Take 250mL of 20mg / L Orange II (Acid Orange 7, AO7) aqueous solution and place it in a 500mL beaker, put the beaker in a 30°C water bath, add 3mmol / L hydrogen peroxide (3mmol hydrogen peroxide is added to each liter of wastewater), adjust the pH value to 4.1 by adding 5% dilute sulfuric acid solution, mechanically stir the Orange II solution at 600r / min, add 0.5g / L pre-oxidized iron-based amorphous alloy strips, and take 4.8mL of Orange II solution at 0s, 30s, 60s, 90s, 2.5min, 4min, 6min and 9min after the strips are added, filter through a 0.22μm water-based polyethersulfone (PES) filter membrane, measure the solution spectrum by a UV-visible photometer, calculate the degradation rate of Orange II in the solution at different times and draw a degradation rate curve.
[0108] Fig. 20 (a) is the UV-visible absorption spectrum measured in Example 11, Fig. 20 (b) is a curve showing the degradation rate variation over time of the 1k107 Fe-based amorphous strip pre-oxidized and activated at 750° C. in Example 11 when degrading a 20 mg / L Orange II aqueous solution; Fig. 20 (b) shows that the degradation rate of Orange II (AO7) is 86.7% after 4 min reaction under the above degradation conditions, and after 9 min, its degradation rate reaches 97.8%.
[0109] Example 12
[0110] The same as Example 1, except that the pH of the solution was adjusted to 4.5 instead of 3.0, and 4.8 mL of Orange II solution was taken at 0s, 0.5min, 1min, 1.5min, 2.5min, 4min, 6min, 9min, 13min, 18min and 25min after the strip was added, and the solution was filtered through a 0.22μm aqueous polyethersulfone (PES) filter membrane, and the solution spectrum was measured using a UV-visible photometer.
[0111] Figure 5 (c) is the UV-visible absorption spectrum obtained in Example 12. Fig.17 This is a degradation rate curve of the Orange II dye aqueous solution in Example 12. The degradation rate of Orange II is 53% after 25 minutes of reaction under the degradation conditions.
[0112] Example 13
[0113] The same as Example 1, except that, in step 1), the high temperature oxidation treatment condition is changed from 650°C oxidation for 5 min to 850°C oxidation for 1 min, and in step 2), the sampling time is changed to 0 min, 1 min, 3 min, 5 min, 9 min, 13 min, 18 min, and 25 min.
[0114] Figure 6 (a) is the UV-visible absorption spectrum obtained in Example 13. Fig.18 This is a degradation rate curve of the Orange II dye aqueous solution in Example 13. The degradation rate of Orange II is 37% after 25 minutes of reaction under the degradation conditions.
[0115] Comparative Example 1
[0116] 1) Place 0.25g of Fe-based amorphous 1K107 strip in air at 200°C and leave it for 20 minutes to simulate the state of 1K107 strip in service for 5-10 years at room temperature. Take out the oxidized Fe-based amorphous strip and cool it in air for use as a waste (aged) amorphous strip simulating long-term service.
[0117] 2) Take 250 mL of 20 mg / L Orange II aqueous solution and place it in a 500 mL beaker. Place the beaker in a 30°C water bath and add 3 mmol / L hydrogen peroxide to adjust the pH to 3.
[0118] 3) The Orange II solution was mechanically stirred at 350 r / min, 0.125 g of the simulated long-term service waste (aged) amorphous strip (0.5 g / L) in step 1) was added, and 4.8 mL of the Orange II solution was taken at 0 min, 1 min, 3 min, 5 min, 9 min, 13 min, 18 min and 25 min after the strip was added, respectively, and the solution was filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane, and the solution spectrum was measured using a UV-visible photometer. The degradation rate of Orange II in the solution at different times was calculated and the degradation rate curve was plotted.
[0119] Figure 8 (b) is the UV-visible absorption spectrum of Comparative Example 1, and it can be seen that Orange II did not begin to degrade in the first 25 minutes under the degradation conditions. Compared with Example 9, it is shown that the degradation ability of the iron-based amorphous strips that have been in service for 5-10 years at room temperature to Orange II is relatively poor, and after high-temperature oxidation treatment at 650°C in air for 5 minutes, the degradation ability is greatly improved.
[0120] Comparative Example 2
[0121] 1) Take 250 mL of 20 mg / L Orange II aqueous solution and place it in a 500 mL beaker. Place the beaker in a 30°C water bath and add 3 mmol / L hydrogen peroxide to adjust the pH to 3.
[0122] 2) The Orange II solution was mechanically stirred at 350 r / min, 0.125 g of iron-based amorphous 1K107 strip (0.5 g / L) was added, and 4.8 mL of Orange II solution was taken at 0 min, 1 min, 3 min, 5 min, 9 min, 13 min, 18 min, 25 min and 90 min after the strip was added, respectively. The solution was filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane, and the solution spectrum was measured using a UV-visible photometer. The degradation rate of Orange II in the solution at different times was calculated and the degradation rate curve was drawn.
[0123] Fig. 9 The ultraviolet visible light absorption spectrum diagram measured for comparative example 2 shows that Orange II dye has an absorption peak at 485nm, and the degradation rate of Orange II dye is calculated based on this peak. It can be seen that Orange II does not begin to degrade in the first 25min under the degradation conditions. After 90min of reaction, the degradation rate of Orange II is only 72.2%. Compared with Example 1, it is shown that the degradation ability of the iron-based amorphous strips that have not been strengthened by high-temperature oxidation treatment to Orange II is relatively poor, even low concentration (20mg / L) of azo dyes still requires a long time to degrade, and the degradation is insufficient, and the degradation rate of more than 99% cannot be achieved.
[0124] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for treating organic pollutants in wastewater by strengthening iron-based amorphous alloys using a pre-oxidation activation method, characterized in that: The following steps are involved: The wastewater containing organic pollutants is heated, hydrogen peroxide is added, the pH is adjusted, and then the pre-oxidized iron-based amorphous alloy is added and reacted under stirring to degrade the organic pollutants.
2. The method for treating organic pollutants in wastewater by using pre-oxidation activation method to strengthen iron-based amorphous alloy according to claim 1, characterized in that: The concentration of the organic pollutants in the wastewater is 5-350 mg / L, the amount of hydrogen peroxide added is 1-30 mmol / L, and the amount of pre-oxidized iron-based amorphous alloy added is 0.05-20 g / L.
3. The method for treating organic pollutants in wastewater by using pre-oxidation activation method to strengthen iron-based amorphous alloy according to claim 1, characterized in that: The pre-oxidized iron-based amorphous alloy is subjected to high-temperature oxidation treatment in air or an atmosphere with an oxygen partial pressure of not less than 0.01 MPa to obtain the pre-oxidized iron-based amorphous alloy.
4. The method for treating organic pollutants in wastewater by using pre-oxidation activation method to strengthen iron-based amorphous alloy according to claim 3, characterized in that: The temperature of the high temperature oxidation is 450-850° C., and the time is 6 seconds to 30 minutes.
5. The method for treating organic pollutants in wastewater by using pre-oxidation activation method to strengthen iron-based amorphous alloy according to claim 4, characterized in that: The temperature of the high temperature oxidation is 500-800°C.
6. The method for treating organic pollutants in wastewater by using pre-oxidation activation method to strengthen iron-based amorphous alloy according to claim 5, characterized in that: The temperature of the high temperature oxidation is 650-750°C.
7. The method for treating organic pollutants in wastewater by using pre-oxidation activation method to strengthen iron-based amorphous alloy according to claim 3, characterized in that: The iron-based amorphous alloy includes one or more of newly prepared amorphous strips by casting or smelting, strips with partially aged and crystallized surfaces, and waste strips with rusted and oxidized surfaces. The iron-based amorphous alloy includes silicon, boron and iron, wherein the mass percentage of iron atoms is ≥50%.
8. The method for treating organic pollutants in wastewater by using pre-oxidation activation method to strengthen iron-based amorphous alloy according to claim 1, characterized in that: The heating temperature is 10-80° C., the pH is 2.0-6.5, and the stirring time is 10s-30min.
9. The method for treating organic pollutants in wastewater by using pre-oxidation activation method to strengthen iron-based amorphous alloy according to claim 1, characterized in that: The organic pollutants include one or more organic substances such as Orange II, methylene blue, rhodamine B and phenol.
Citation Information
Patent Citations
A method and apparatus for preparing and applying iron-based nanocrystalline alloys for treating dyeing and printing wastewater containing azo dyes.
CN107326159B
Iron-based porous material for degrading azo dye and preparation method of iron-based porous material
CN109402369A
A series of iron-based amorphous alloy strips, their preparation method, and their application in degrading azo dye wastewater.
CN110918911B
Method for Degrading Dye Wastewater with Iron-Based Amorphous Alloy Strips
CN111170414B
A strip-shaped amorphous alloy catalyst with a nanostructure, its preparation method and application
CN112973691B